(untitled) - Hill, L. A. (Oxford, 1980)
"Anecdotes in American English are three highly-motivating, humorously-illustrated readers that will appeal to a wide range of students. Each book contains thirty amusing anecdotes, followed by comprehension questions and vocabulary exercises to stimulate class discussion. An appendix in each book lists all the vocabulary items in the text. A "Cassette containing the complete text of the reading passages and the comprehension question is available for each book.
Keywords: English language,Readers